Start-up and steady-state conditions of an Anaerobic Hybrid Reactor (AHR) using mini-filters composed with two types of support medium operating under low loading rates - Silva,Vivian Galdino da (2011)
The present work aimed at studying the operational parameters of an Anaerobic Hybrid Reactor (AHR) removing organic matter of coffee wastewater with low concentration. The AHR was built similar to an UASB reactor, however the interior was filled with mini-filters composed by two types of support materials: expanded clay and rolled pebble. Three start-ups were accomplished in order to achieve the stationary state (steady-state). Three hydraulic retention times were appraised: 28.5; 24.0 and 18.0 h, obtaining a volumetric loading rate (VLR) of 0.70; 0.56; 0.54 kg COD m-3 d-1 and a biological organic loading rate (BOLR) of 0.0156; 0.0103 and 0.01213 kg BOD5 kg TVS-1 d-1. Due to the decrease in the concentration of organic matter in the influent, the endogen process started to occur on the biomass lowering the methanogenic process.